FOREIGNIZATION AND DOMESTICATION IN TRANSLATING INDONESIAN CULTURE-SPECIFIC TERMS IN THE ENGLISH SUBTITLES OF THE MOVIE TABULA RASA - Sandi, Nanda Alisha (2016)
The present study seeks to investigate translation strategies related to foreignization and domestication of cultural terms found in the English subtitles of the movie Tabula Rasa. Descriptive qualitative method has been used as the methodology of this study because it deals with data in the form of text. Pedersen's (2005) translation strategies and Newmark's (1988) cultural terms are used as the theoretical framework. The results show that domestication is the most frequently used translation strategy in translating Indonesian cultural terms (88%). However, the translator still attempted to maintain certain aspects of the Indonesian culture in the target language text by preserving names of Indonesian food. Keywords: Foreignization, domestication, translation strategies, cultural words ---------- Penelitian ini dilakukan untuk menginvestigasi strategi penerjemahan yang berkaitan dengan foreignization dan domestication dalam menerjemahkan cultural terms yang diteukan pada subtitle bahasa Inggris dari film Tabula Rasa. Metode yang dilakukan dalam penelitian ini adalah deskriptif kualitatif, mengingat penelitian ini mengambil data dalam bentuk teks. Penelitian ini menggunakan teori dari Pedersen (2005) tentang strategi penerjemahan dan teori dari Newmark (1988) tentang cultural terms. Hasil penelitian ini memperlihatkan bahwa strategi domestication merupakan strategi yang paling banyak diguakan dalam menerjemahkan cultural terms yaitu sebesar 88%. Namun, penerjemah masih berupaya untuk menampilkan beberapa aspek dari kultur Indonesia dalam subtitle bahasa Inggris dengan menggunakan strategi preservation, dan tidak menerjemahkan beberapa kata yang berkaitan dengan kultur Indonesia.